1993
DOI: 10.1128/mcb.13.6.3125
|View full text |Cite
|
Sign up to set email alerts
|

A 5'-3' exonuclease from Saccharomyces cerevisiae is required for in vitro recombination between linear DNA molecules with overlapping homology.

Abstract: When two linear DNA molecules with overlapping, homologous ends were incubated with a yeast nuclear extract, they recombined at the region of homology to produce a joint molecule. We have identified a 5'-3' exonuclease in the extract that is likely to be responsible for the formation of the observed product. We propose that the exonuclease degrades each substrate to reveal regions of complementary sequence which anneal to form a recombinant product. Consistent with this model, we have partially purified the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…The activity of the exonuclease to lead recombinant formation should be significantly lower in rate than that in the Mre11 complex but should be enough to attain a wild-type level at least. One of the candidate genes of the exonuclease may be the EXO1 gene (12,17), which is a multicopy suppressor of the MMS sensitivities of mre11 and rad50 deletions (45a). Why does another exonuclease not substitute for the meiotic recombination defect of the mre11-58 mutation?…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the exonuclease to lead recombinant formation should be significantly lower in rate than that in the Mre11 complex but should be enough to attain a wild-type level at least. One of the candidate genes of the exonuclease may be the EXO1 gene (12,17), which is a multicopy suppressor of the MMS sensitivities of mre11 and rad50 deletions (45a). Why does another exonuclease not substitute for the meiotic recombination defect of the mre11-58 mutation?…”
Section: Discussionmentioning
confidence: 99%
“…This resection may be necessary for strand exchange to be initiated in homologous recombination, but results of others (3a) also suggest that the 3'-to-5' activity of HPP1 may be required for end joining. Recent evidence from reactions involving extracts of both Xenopus oocytes and yeast nuclei also shows that exonuclease digestion is an important component in the homologous recombination of linear DNA molecules with overlapping homology (10,15). Alternatively, it is not implausible that the opening up of the termini to allow single-strand annealing between the partners might be accomplished by helicases.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work aimed at developing an in vitro system for recombination in S. cerevisiae, we identified a 5Ј-3Ј exonuclease that was required for an end-joining reaction and for the formation of joint molecules between two linear duplexes that had a region of overlapping terminal homology (20,51). Because this activity was undiminished in cell extracts prepared from a strain containing mutations in the NUC1 and SEP1 genes, we concluded that it was distinct from these previously characterized exonucleases.…”
mentioning
confidence: 89%